Shrinkage in Portuguese National Policy and Regional Spatial Plans: Concern or Unspoken Word? - Sousa, Sílvia; Pinho, Paulo (Journal of Tourism, Sustainability and Well-being, 2014)
This paper aims to assess whether and how current Portuguese national spatial planning policy and regional spatial plans are based on evidence revealing trends and patterns of population decrease and rural and urban shrinkage in Portugal. Firstly, built on a literature review, we identify the consequences of population decrease, the so-called characteristics of shrinkage, and we briefly look at dominant approaches and strategies to deal with it. Secondly, we review macro level policy documents to access global awareness and perception of shrinkage from a transnational perspective. Finally, after sketching an international framework on our subject matter shrinkage, a content analysis is applied to the Regional Spatial Plans of the Metropolitan Area of Lisbon and of the Northern Region. Urban shrinkage and shrinking cities are not explicitly mentioned in these documents. This is partly understandable because it is an emergent phenomenon in Portugal, in comparison with other countries, and because the concept is recent and it has not yet come to light in Portuguese planning practice. In addition, results suggest that the doctrine of growth is still embedded in Portuguese planning culture. In sum, despite clear evidence of population decrease in Portugal, spatial planning policy and regional spatial plans have either disavowal or reactive character pertaining population decrease and shrinkage.